Frequency of Measles with Complications in COVID Pandemic (Medical Forum Monthly, 2021)
Objective: To determine the frequency of measles with complications in covid-19 pandemic.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Department of Paediatrics, Saidu Group of Teaching Hospitals, Swat from December 2020 to May 2021.Materials and Methods: Three hundred and eighty-seven children were enrolled. Demographic information such as anthropometry, measles complications, vaccination history, and prior outcome of measles patient’s admission within 15 days was taken from institute records.Results: The prevalence of unvaccinated subjects was 113 (29.2%). The measles complications involve an unvaccinated state, encephalitis, and being stunted as compared to pneumonia (p<0.05). Within 15 days of admission, 35 (9%) children died.Conclusion: The fatality rate from measles complications was 9% in the study population. Half of the children were vaccinated despite having measles complications. Non-vaccination, malnutrition, and encephalitis were associated with a higher risk of death from measles complications.